Patterns of myocardial involvement in children during COVID-19 pandemic: Early experience from northern Italy - Paolo Ferrero; Isabelle Piazza; Caterina Bonino; Matteo Ciuffreda (Wolters Kluwer Medknow Publications, 2020)
There is limited information about coronavirus disease 2019 (COVID-19) in the pediatric population. Preliminary data suggest a not insignificant prevalence of cardiac involvement. Here, we report our early experience with COVID-19 in the pediatric population. These patients display exceptionally high levels of acute-phase reactants. The clinical syndrome in these patients is somewhat similar to Kawasaki disease with or without myocardial involvement. In some cases, the presentation mimics typical myocarditis. Severe myocardial involvement is associated with transient electrocardiographic and echocardiographic abnormalities. These findings may be due to the cardiotropic nature of the virus or may be the result of an immunologic response to the infection.